Effect of myopia and astigmatism deepening on the corneal biomechanical parameter stress-strain index in individuals of Chinese ethnicity - Liu, Yan; Pang, Chenjiu; Ming, Shuai; Fan, Qi (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To investigate the difference of corneal biomechanical parameter stress-strain index (SSI) in different degrees of myopic eyes, and to analysis the relevant factors of SSI in Chinese myopic population. Methods: This study enrolled 474 myopic eyes from 474 participants (18-34 years old), only the right eyes were included. The participants was divided into four groups according to their spherical equivalent (SE), 66 eyes in low myopia group, 260 eyes in moderate myopia group, 102 eyes in high myopia group, and 46 eyes in ultra-high myopia group. Spherical, cylinder and SE were measured via automatic integrated optometry. Intraocular pressure (IOP) was measured using non-contact tonometer. AL was measured using IOLMaster. Corneal curvature and central corneal thickenss (CCT) were measured using Pentacam. SSI and bIOP was measured via corneal visualization Scheimpflug technology (Covris ST). One-sample Kolmogorov-Smirnov test and normal distribution histogram method, Levene variance homogeneity test, Pearson correlation analysis, multiple linear stepwise regression analysis, one-way ANOVA and LSD-t test were used for ststistical analyses. Results: The mean (±SD) age of 474 participants was (23.70±4.65)years old, with the 95% CI of 23.27-24.14 years old. SSI was positively correlated with spherical, cylinder, SE, CCT, IOP, and bIOP, negatively correlated with K1 and AL (r=0.384, 0.279, 0.404, 0.145, 0.306, 0.184, -0.103, -0.371; all P<0.05), but not correlated with age, K2, or Km (all P>0.05). Multiple linear regression analysis was performed with SSI as the dependent variable, and spherical, cylinder, K1, CCT, and IOP as independent vavariables, the following regression equation was obtained: SSI=0.961+0.017 spherical+0.042 cylinder + 0.018 IOP (R2=0.306, F=41.210, P<0.001). SSI values in low myopia, moderate myopia, high myopia, and ultra-high myopia groups were 0.958±0.124, 0.921±0.118, 0.876±0.114 and 0.763±0.112, which decreased sequentially, and the differences were statistically significant in pairs (all P<0.05). Conclusion: SSI value decreases gradually as myopia deepening in Chinese myopic eyes, which is lowest in ultra-high myopia eyes. SSI change is mailnly dependent on the degree of myopia, and less dependent on CCT and IOP, the variation of SSI may be related to the pathogenesis of myopia.